Pengaruh Model Project Based Learning pada Materi Virus Terhadap Kreativitas Peserta Didik SMAN 13 Banjarmasin - Aminuddin Prahatama Putra; Bunda Halang; Rizki Amalia Putri (EduInovasi: Journal of Basic Educational Studies, 2025)
Students can support their learning process and, of course, acquire a variety of key creativity being one of them by using the Project Based Learning (PjBL) paradigm, besides that it is very suitable in the implementation of the independent curriculum. However, SMAN 13 Banjarmasin school has never applied this learning method in biology learning, especially virus material. This study was to find out how PjBL instruction on virus material affected the class X students at SMA Negeri 13 Banjarmasin's capacity for creative thought. The research strategy utilized is a quasi-experiment, with a control group pre-test-post-test. PjBL learning is applied in one class as an experimental class, and direct instruction learning model—a learning model that is typically implemented—is applied in the control class. The N Gain test and the Mann Whitney U test, which compares the control and experimental classes, are the analysis techniques employed. Because the level of significance was 0.001 <0.05, analysis based on hypothesis testing demonstrated that the PjBL model had a substantial impact on creative thinking skills when compared to the conventional model. The results of this research support the conclusion that applying the PjBL model significantly improves students' capacity for creatuve thinking skills, which is measured using four criteria: 1) Fluency; 2) Flexibility; 3) Originality; and 4) Elaboration.